Cops, Teachers, and the Art of the Impossible: Explaining the Lack of Diffusion of Innovations That Make Impossible Jobs Possible. (14th December 2012) - Maranto, Robert; Wolf, Patrick J.
<x xml:space="preserve">Abstract</x> In their 1990 book Impossible Jobs in Public Management, Erwin C. Hargrove and John C. Glidewell argue that public agencies with limited legitimacy, high conflict, low professional authority, and weak agency myths have essentially impossible jobs. Yet some such positions have proven operationally possible. For example, over a 17‐year period, the New York City Police Department achieved dramatic reductions in crime. A second impossible job discussed by James Q. Wilson, the urban school superintendent, has also proven possible, with Washington, D.C., having considerable success educating disadvantaged children. However, these successes in urban crime control and public schooling have not been widely copied. Building on the work of Manuel P. Teodoro, the authors use these cases to discuss how the inflexibility of personnel systems and political costs of disruptive reforms combine with the professional norms and progressive ambition of agency leaders to limit the diffusion of innovations in law enforcement and schooling. The article concludes with hypotheses for future testing.